Multidimensional Physical Activity: An Opportunity, Not a Problem. Issue 2 (April 2015) - Thompson, Dylan; Peacock, Oliver; Western, Max; Batterham, Alan M.
Abstract : Our research shows that no single metric will reflect an individual's physical activity adequately because multiple biologically important dimensions are independent and unrelated. We propose that there is an opportunity to exploit this multidimensional characteristic of physical activity to improve personalized feedback and offer physical activity options and choices that are tailored to an individual's needs and preferences. Abstract : We demonstrate how it will be possible to exploit emerging technology to improve the quality of informational physical activity feedback.